RHS Photographers Shoot Area Scenes, show works at Old Pass (Raton Range Raton, NM, 1993)
Talks about High School Students taking photographs to show at the Old Pass Gallery as a special exhibit in conjunction with the Museum of New Mexico's Traveling Exhibition.
Newspaper article
Master list item #: 23
File location is in the Raton file Cabinet
Keywords: Newton, Mary -- Art Teacher -- Raton, New Mexico; Raton High School; Des Moines High School; Marshall L. and Perriene D. McCune Foundation; Museum of New Mexico; Raton Museum; Folsom Museum; Old Pass Gallery; Photography Shows; Art Show; Art Exhibits; Local Artist; Student Photography; Raton, New Mexico; Folsom, New Mexico; Des Moines, New Mexico; Capulin, New Mexico